2018
DOI: 10.1002/ijc.31346
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of the Notch pathway enhances the efficacy of androgen deprivation therapy for prostate cancer

Abstract: Although androgen deprivation therapy (ADT) is a standard treatment for metastatic prostate cancer, this disease inevitably recurs and progresses to ADT-resistant stage after this therapy. Accordingly, understanding the mechanism of resistance to ADT and finding new approach to enhance the efficacy of ADT may provide a major benefit to PCa patients. In our study, we found upregulated expression of Notch receptors is positive associated with ADT-resistance progression. Using fluorescent Notch signaling reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Recent studies demonstrate that Notch3 is involved in normal prostate development where it is required for luminal cell differentiation (11,14,15). Furthermore, elevated Notch3 expression positively correlates with prostate cancer progression, recurrence, and drug resistance (16)(17)(18)(19)(20). In metastatic breast cancer, Jag-1 in tumor cells activates Notch signaling in osteoblasts to stimulate osteoclastogenesis in osteolytic bone lesions, while Notch3 is induced in tumor cells by osteoblasts (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that Notch3 is involved in normal prostate development where it is required for luminal cell differentiation (11,14,15). Furthermore, elevated Notch3 expression positively correlates with prostate cancer progression, recurrence, and drug resistance (16)(17)(18)(19)(20). In metastatic breast cancer, Jag-1 in tumor cells activates Notch signaling in osteoblasts to stimulate osteoclastogenesis in osteolytic bone lesions, while Notch3 is induced in tumor cells by osteoblasts (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Notch inhibition was shown to overcome resistance to androgen deprivation in PCa cells, strengthening the link between Notch and AR signaling. 31 VCaP AR expression may explain the lack of difference in proliferation of OMP-A2G1-treated tumors. Another possibility is the ERG expression present in VCaP but not DU145.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, elucidating the mechanisms of resistance to ADT is necessary. Three recent studies have shown that Notch signalling can contribute to resistance to enzalutamide (androgen receptor antagonist) [46] and that Notch inhibition combined with ADT can cause a synergistic therapeutic effect [47,48]. In addition, Notch signalling has also been implicated in docetaxel resistance [49].…”
Section: Discussionmentioning
confidence: 99%